Densification behaviour and three-dimensional printing of Y2O3 ceramic powder by selective laser sintering. Issue 6 (15th March 2021) - Ratsimba, A.; Zerrouki, A.; Tessier-Doyen, N.; Nait-Ali, B.; André, D.; Duport, P.; Neveu, A.; Tripathi, N.; Francqui, F.; Delaizir, G.
Abstract: The selective laser sintering (SLS) of an yttria (Y2 O3 ) ceramic powder was studied to understand both the effects of i) the initial yttria particle characteristics on the powder bed behaviour and ii) the process conditions (laser power, scanning speed, hatching space) on the sintering/melting of three-dimensionally printed objects. The roughness of the powder bed, a sensitive indicator of the layer bed quality, was determined through three-dimensional optical profilometry and the powder bed packing density was modelled using the discrete-element method. Complex shaped objects including spheres and open rings were successfully fabricated by the SLS three-dimensional printing. In addition, SLS cube-shaped samples were characterized by X-ray diffraction and scanning electron microscopy. The open pore volume fraction significantly decreased from 41% without a post-SLS heat treatment to 31% with a post-SLS heat treatment at 1750 °C for 20 h under secondary vacuum. Finally, an anisotropy in elastic properties has been highlighted, Young's modulus reaches 11 GPa in the stiffest direction.